Engaging SMEs in an e-Learning Programme - Stewart, Jean-Anne; Alexander, Gillian (Proceedings of the International Conference on Networked Learning, 2006)
This paper presents the findings from a project investigating management development for SME managers using an action learning programme, combining both face-to-face workshops and e-learning. This programme was undertaken as part of ENSeL (Engaging Networks for Sustainable eLearning), which was supported by the European Commission. The project aimed to address 3 main objectives: reworking results from previous European projects to disseminate to a wider audience, creating a learning network amongst the project partners and to undertake 3 learning trials with SMEs in UK, France and Italy. This paper principally addresses the findings from the UK trials, which ran between February and April 2005, and provides valuable learning to all those interested in developing future learning programmes aimed at SMEs.